Strategies of Localizing Video Games into Arabic: A Case Study of PUBG and Free Fire - Jarrah Shatha; Haider Ahmad S.; Al-Salman Saleh (Open Cultural Studies, 2023)
Video game localization is the process of adjusting a current video game to make it available, usable, and culturally appropriate to the target audience. This study aims to investigate the strategies that translators use in localizing PUBG and Free Fire video games into Arabic. The data were extracted from interfaces and in-game captions of the two video games. Due to space constraints, a representative subset of the collected data was then selected and analysed according to the translation strategies proposed by Díaz-Cintas, and Remael (2014). The analysis showed that the localizers have more often used transposition and literal translation strategies. They also tried to adapt the text to suit the target-language culture as much as possible. The findings of this study will be helpful to translators, localizers, and trainers. By adopting the most relevant translation strategies outlined in this article, game localizers will hopefully be better equipped with the mechanisms of video game localization. The current piece of work calls for investing more research efforts towards exploring and targeting a broader array of video game genres in Arabic.